The impact of proton pump inhibitors on bone regeneration and implant osseointegration. (3rd July 2019) - Mester, Alexandru; Apostu, Dragos; Ciobanu, Lidia; Piciu, Andra; Lucaciu, Ondine; Campian, Radu Septimiu; Taulescu, Marian; Bran, Simion
Abstract: Proton pump inhibitors (PPIs) have become known for the treatment of gastric-acid related disorders. Similar to any other drugs, PPIs have possible adverse reactions, being associated with bone fractures, infections, kidney disease, mineral deficiency, dementia, and pneumonia. Multiple analyses have stated that PPIs therapy may affect bone regeneration and osseointegration process, causing an increased risk of bone fracture, deterioration of bone metabolism and impaired bone healing. In this review, we emphasized the current literature regarding the influence of proton pump inhibitors in the bone regeneration process. Results from the studies suggest a link between PPIs intake and bone regeneration, but several concerns are raised regarding inadequate recipient bone, surgical trauma, limitations on the titanium surface, comorbidities or interference with other pharmacological agents. Further studies are needed to determine whether the impaired bone regeneration process is due to PPI or coexisting factors.